Research of factors of development of agriculture in Ukraine: methodical approach on the basis of econometric modeling - Danko, Yuriy; Nifatova, Olena; Orel, Volodymyr; Zhmailov, Valeryy; Lutska, Tetiana (My University, 2022)
The article examines the factors of agricultural development in Ukraine. The study of agricultural production growth reserves was carried out using the production function as a basis for modeling economic development. Considering that the income of the industry is formed under the influence of a combination of factors of extensive and intensive growth, we conducted a correlation and regression analysis of the impact of groups of selected factors on the economic growth of agricultural production. The result of the decomposition of the general variation of the real output of agricultural products of Ukraine into factors made it possible to draw the following conclusion: the potential for extensive growth of agricultural production by attracting additional land and human resources is exhausted. At the present stage of development of agriculture in Ukraine, the main factor in the growth of real agricultural output is to increase productivity. У статті досліджено чинники розвитку сільського господарства України. Дослідження резервів зростання сільськогосподарського виробництва здійснено з використанням виробничої функції як основи моделювання економічного розвитку. Враховуючи, що дохід галузі формується під впливом поєднання факторів екстенсивного та інтенсивного зростання, нами проведено кореляційно-регресійний аналіз впливу груп виділених факторів на економічне зростання сільськогосподарського виробництва. Результат розкладу загальної варіації реального виробництва сільськогосподарської продукції України на фактори дав змогу зробити такий висновок: потенціал екстенсивного зростання сільськогосподарського виробництва шляхом залучення додаткових земельних і людських ресурсів вичерпано. На сучасному етапі розвитку сільського господарства України основним чинником зростання реального обсягу продукції сільського господарства є підвищення продуктивності праці.
Keywords: agriculture; enterprise economics; development factors; modeling; сільське господарство; економіка підприємства; фактори розвитку; моделювання; кафедра економіки і права